Pelatihan Literasi Keuangan dan Keuangan Inklusif Pada Kelompok UMKM Purna Migran Desbumi Wonosobo - Alvian Alvin Mubarok; Muhamad Ridwan; Heri Susanto; Zulfikar Muhamad Hasan; Yoga Religia (JEPEmas: Jurnal Pengabdian Masyarakat (Bidang Ekonomi), 2023)
Financial literacy is one of the programs launched by the Financial Services Authority (OJK) to instill knowledge related to financial service products and how to access them. The 2019 National Survey of Financial Literacy and Inclusion (SNLIK) showed a financial literacy index of 38.03% and a financial inclusion index of 76.19%. This shows that the level of knowledge regarding financial service products is still quite low. The MSMEs of the Desbumi Wonosobo Retired Migrant Women's Community is a community group that needs attention. This group is a group of women who have stopped working after becoming female workers (TKW) and have no income. The Social Analysis and Research Institute (SARI) provides training in the form of financial literacy and financial inclusion seminars to increase knowledge about financial service products. It is hoped that this knowledge can provide guidelines for accessing capital in financial service institutions, in this case banks